Wood anatomical features and natural resistance of planted Azadirachta excelsa and Khaya ivorensis - Abdullah Siam, Nordahlia; Lipeh, Shahlinney; Uyup, Mohd Khairun Anwar; Mohd Yusoff, Nur Syauqina Syasya; Talip, Noraini; Abdullah, Nor Azahana; Che Amri, Che Nurul Aini (Innovative Scientific Information Services Network, 2024)
Plantation species such as Azadirachta excelsa and Khaya ivorensis has gained traction as alternative raw materials for timber industry in Malaysia. This present study,was conducted to examine the anatomical features and resistance of the 10-year-old planted A. excelsa and K. ivorensis to white rot fungus (Lentinus sajor-caju). Both A. excelsa and K. ivorensis were easily identified by its anatomical features which were parenchyma, ray, fibre and prismatic crystal. A. excelsa and K. ivorensis wood were classified as resistant, with K. ivorensis being more resistant to white rot fungus, Lentinus sajor-caju. The resistance of the wood to fungal decay decreased towards the top and higher resistance was shown in the heartwood than the sapwood portion. Based on this finding, density could not be an indicator of decay but the resistance of wood is related to the presence of extractives.